(untitled) (Research, Society and Development, 2024)
The Corn Snake (Pantherophis guttatus – Linnaeus, 1766) is a species of snake from the Colubridae Family of American origin, and therefore exotic in Brazil, being a good example of na experimental model due to its adaptability to the national terroir. Carnivores, oviparus and constrictors have satisfactory development in captivity when in na environment whit controlled and ideal parameters of temperature, relative humidity, light and food, necessary for physiological mainstenance of this species. The use of prhototherapy in animals and humans has been demonstrated as a non-invasive treatment, which contributes to the improvement of systemic tissue oxygenation, tissue repair and, consequently, biomodulates the organic system nad immunity, generating positive effects that reflect on the development of individuals. This experimental trial aimed to observe and prove whether systemic, transcutaneous vasculas phototherapy promote benefits and biomodulated the organic system of P. guttatus snakes raised in animal facilities, in order to reflect on development, increased fees conversion, weight gain and lenght body oh this species.